2015
DOI: 10.2334/josnusd.57.195
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield unit comparison of grafted versus non-grafted extraction sockets

Abstract: Volumetric changes of the alveolar ridge after socket preservation with various techniques have been investigated frequently. However, changes in bone density and quality of bone within the extraction sockets have seldom been studied. The purpose of this study was to evaluate the bone quality of grafted versus non-grafted socket sites prior to dental implant placement using Hounsfield unit (HU) values derived from cone-beam computed tomography (CBCT) imaging. The data was collected from 39 healed extraction si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The results obtained are comparable with those of previous studies conducted by Madan et al , and Loveless et al [1920]…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained are comparable with those of previous studies conducted by Madan et al , and Loveless et al [1920]…”
Section: Discussionsupporting
confidence: 92%
“…Many strategies adopted immediately after extraction have proven to maintain bone dimensions. 26 The process of resorption and bone remodeling is more intense in the first three months after extraction and the control of this process remains a challenge in Dentistry. At 30 days, it was observed that bone formation was more advanced in sockets filled with HA, whereas at 90 days treated and control sockets had similar bone density pattern, showing that the biomaterial had a positive influence in the beginning of the alveolar healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Hounsfield units (HU) is a controversial subject in the literature since the consistency and accuracy of the values remain elusive. 26 On the other hand, a study 24 carried out morphometric analysis using the software KS300, applying the gray intensity to compare bone formation in images captured by CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…The change in bone density before and after the ARP measures has been calculated in addition to metric analysis of bone levels [16]. The analysis of CBCT scans regarding radiologically measured bone density was introduced as a method to evaluate the ARP measures [17].…”
Section: Introductionmentioning
confidence: 99%